An adjustment in regulation policies and its effects on market supply: Game analysis for China's rare earths. (December 2015) - Han, Aiping; Ge, Jianping; Lei, Yalin
Abstract: In this context, this paper analyses the scenario in which China abolishes export restrictions and the resulting effects on firms at home and abroad by building a static game-theoretic model. We also establish a dynamic game-theoretic model with complete information to simulate another scenario that China enhances resource tax and levies an environmental tax and to evaluate its effects on firms in China and abroad in different tax rates. The results show that when abolishing rare earths export restrictions, China's rare earths production and export will increase; while rare earths production, domestic supply and price in foreign country will decrease. Moreover, if the Chinese government enhances resource taxes and levies an environmental tax, the production, domestic supply, and exports of rare earths will decrease in China, whereas the opposite effects will exist in other countries. Furthermore, a reasonable rate for the resource and environmental tax should be identified because it is the key factor affecting the market supply in China and abroad. Finally, several policy implications for the Chinese and other governments are proposed. Highlights: China's regulation priority is given to domestic exploitation and production control. A static game model is built to evaluate the effects of abolishing export restriction. A dynamic game model is built to analyze the effects of improving domestic control. 4/7–1 times export tariff rate is a reasonable choice for domestic tax rate.